Integrative Analysis of lncRNAs in Th17 Cell Lineage to Discover New Potential Biomarkers and Therapeutic Targets in Autoimmune Diseases - Teimuri, Shohreh (Mol Ther Nucleic Acids, 2018)
Th17 cells play a critical role in the pathogenesis of autoimmune diseases, including multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus, Sjogren’s syndrome, and inflammatory bowel disease. Despite the extensive investigation into this T cell lineage, little is understood regarding the role of Th17 lineage-specific lncRNAs (long non-coding RNAs) > 200 nt. lncRNAs may influence disease through a variety of mechanisms; their expression could be regulated by SNPs. lncRNAs can also affect the expression of neighboring genes or complementary miRNAs, and their expression may have lineage-specific patterns. In the system biology study presented here, the effective lncRNAs from different criteria were predicted for each autoimmune disease, and we then evaluated their expression levels in 50 MS patients compared to 25 controls using qRT-PCR. We identified changes in the expression levels of AL450992.2, AC009948.5, and RP11-98D18.3 as potential peripheral blood mononuclear cell (PBMC) biomarkers for MS among our studied lncRNAs in which co-expression analysis of AL450992.2 had the most AUCs, and the relationship to RORC was also assessed. We propose that the recurrently deregulated lncRNAs identified in this report could provide a valuable resource for studies aimed at delineating the relationship between functional lncRNAs and autoimmune disorders.